Using Appreciative Inquiry to develop, implement and evaluate a multi-organisation 'Cultivating Compassion' programme for health professionals and support staff. (March 2017) - Curtis, Katherine; Gallagher, Ann; Ramage, Charlotte; Montgomery, Julia; Martin, Claire; Leng, Jane; Theodosius, Catherine; Glynn, Angela; Anderson, John; Wrigley, Martha
The 'Cultivating Compassion' project was developed in response to a research and innovation call relating to compassion training for National Health Service staff in the South East of England. The project aims included the following: the use of Appreciative Inquiry to develop, implement and evaluate a sustainable and evidence-based programme of compassion awareness training through engaging with a diverse group of health professionals and support staff; an evaluation of a 'train the trainers' approach; and an evaluation of 'compassion lead' roles and a multi-modal compassion toolkit. The project team included academics from two universities and one medical school, NHS staff from three separate organisations and service users. The participants recruited to the study included doctors, nurses, receptionists, chaplains and others working in close contact with service users from within four NHS organisations in the South East of England. The main findings from the project using thematic analysis from participant focus groups and interviews identified project enablers and inhibitors, the value of project resources, and shifts in perspectives. Project conclusions highlighted the importance of effective senior-level support and organisational leadership in cultivating compassion within a healthcare organisation and the importance of the integration of compassion-promoting resources within existing staff development initiatives.